2006
DOI: 10.1074/jbc.m601074200
|View full text |Cite
|
Sign up to set email alerts
|

Alkylamides from Echinacea Are a New Class of Cannabinomimetics

Abstract: Alkylamides (alkamides) from Echinacea modulate tumor necrosis factor ␣ mRNA expression in human monocytes/macrophages via the cannabinoid type 2 (CB 2 ) receptor (Gertsch, J., Schoop, R., Kuenzle, U., and Suter, A. (2004) FEBS Lett. 577, 563-569). Here we show that the alkylamides dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide (A1) and dodeca-2E,4E-dienoic acid isobutylamide (A2) bind to the CB 2 receptor more strongly than the endogenous cannabinoids. The K i values of A1 and A2 (CB 2 ϳ60 nM; CB 1 >1500 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(127 citation statements)
references
References 59 publications
5
119
1
Order By: Relevance
“…Both of these alkamides are of special interest. Fractions of alkamide 2 had the highest inhibition of cyclooxygenase-1 and -2, and alkamide 8 exhibited a very strong affinity for the CB 2 cannabinoid receptors (Raduner et al 2006;Woelkart and Bauer 2007). Binding to CB 2 receptors is considered a possible mode of action for the immunomodulatory effects of the alkamides of Echinacea.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Both of these alkamides are of special interest. Fractions of alkamide 2 had the highest inhibition of cyclooxygenase-1 and -2, and alkamide 8 exhibited a very strong affinity for the CB 2 cannabinoid receptors (Raduner et al 2006;Woelkart and Bauer 2007). Binding to CB 2 receptors is considered a possible mode of action for the immunomodulatory effects of the alkamides of Echinacea.…”
Section: Resultsmentioning
confidence: 98%
“…Alkamides trigger enhanced anti-inflammatory activity and immunostimulatory responses (Chen et al 2005;Woelkart et al 2006). Alkamides from Echinacea modulated a therapeutic response via the CB 2 -specific cannabinoid receptor and inhibited lipopolysaccharide-induced inflammation in human whole blood (Raduner et al 2006;Woelkart and Bauer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Echinacea marker compounds have been characterized, including polysaccharides, caffeic acid derivatives (CADs) and alkylamides (Bauer, 1998;Binns et al, 2002), and these have all been shown to possess infectionrelated bio-activities in various tests in vitro and in vivo, including immune-modulating activities, anti-viral activities, and antibiotic activities (Burger et al, 1997;Bauer, 1998;Rininger et al, 2000;Goel et al, 2002;Merali et al, 2003;Gertsch et al, 2004;Vimalanathan et al, 2005;Hudson et al, 2005;Raduner et al, 2006;Sharma et al, 2006;LaLone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…65,74 For instance, NAAs seem to play a major role in the bioactivity of the widely used medicinal plants of the Echinacea genus. 35,[65][66][67][68] The immunomodulatory Echinacea alkylamides dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide ( Figure 2) and dodeca-2E,4E-dienoic acid isobutylamide bind to the cannabinoid-2 (CB 2 ) receptor more strongly than the endogenous cannabinoids. 68 While the interactions of Echinacea NAAs with CB receptors have been studied in more detail, ECS-interacting NAAs from other plants have been described only recently.…”
Section: Analgesic and Anticonvulsant Effectsmentioning
confidence: 99%
“…35,[65][66][67][68] The immunomodulatory Echinacea alkylamides dodeca-2E,4E,8Z,10Z-tetraenoic acid isobutylamide ( Figure 2) and dodeca-2E,4E-dienoic acid isobutylamide bind to the cannabinoid-2 (CB 2 ) receptor more strongly than the endogenous cannabinoids. 68 While the interactions of Echinacea NAAs with CB receptors have been studied in more detail, ECS-interacting NAAs from other plants have been described only recently. 72,73,75,76 The assumption that NAAs may interfere with the ECS due to their structural similarity to endocannabinoids such as anandamide (N-arachidonoylethanolamide, AEA) and palmitoylethanolamide 35 is intuitive, but the confirmation of this assumption is hampered by the lack of structure -activity relationship (SAR) data.…”
Section: Analgesic and Anticonvulsant Effectsmentioning
confidence: 99%